Strategi Bauran Pemasaran Usaha Catering Miracle di Kecamatan Ranotana Weru Kota Manado - Rawis*, Jemmy E O; Pangemanan, Stevy P (Universitas Syiah Kuala, 2023)
This research is a case study research on Miracle catering in the city of Manado. This study aims to describe the 4 P's marketing mix strategy implemented by Miracle Catering. The 4 P marketing mix includes marketing aspects, namely product, price, promotion, and place. The four of them become a single unit that is used to develop a marketing strategy. The results of the study show that the product strategy used is the catering food menu following Chinese food flavors and Minahasa Manado specialties which are in great demand by consumers. Products are offered in menu packages with choices 1 to 4, also serving a menu of pan choices and boxed rice, with the selected price of each package adjusted to the consumer's cost capability which is a pricing strategy. The location of Miracle's catering business is in the Manado city area which is very strategic in purchasing raw materials besides that the location can reach consumers in serving in other areas, namely Minahasa Regency and North Miahasa Regency (place strategy). The promotion strategy carried out is through brochures, the use of online media and word of mouth strategies.